Struktur Komunitas Gastropoda di Kawasan Mangrove Pesisir Suramadu, Surabaya - Nurul Laily; Nur Rohmatin Isnaningsih; Reni Ambarwati, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Structure of Gastropod Communities at Mangrove In Suramadu Coast, Surabaya. The mangrove forest on east coast of Surabaya (Pamurbaya) is reported to be decreasing because it was converted into industrial and residential area. This ecological pressure will affect the fauna living in that area, one of which is gastropods. This study aims to determine the structure of gastropods communities in mangrove of Suramadu coastal area. Sampling was carried out at four different stations using quadrant transect method (1x1 meter plot). Twelve species, members of nine families of gastropods was identified. Semiricinula tissoti (Muricidae) has the highest values of density (d), relative abundance (kr), relative frequency (fr) and importance (inp). The ecological index calculation of the gastropod community from Pamurbaya showed that diversity index (h') ranges from 0.47 to 2.09, dominance index (c) is between 0.14 and 0.79, while evenness index (e) is 0.80 to 0.40. Station I represents the better ecosystem condition compared to the other stations because it has maximum H', E values, and minimum C values. These results indicate that the gastropods species diversity in station I relatively high with an equal number of individual for each species. Dominant species was not found. The ecological conditions at station I are ideal hence the gastropod community is in stable and balanced environment.